Pengaruh Pengawasan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah (BAPPEDA) Provinsi Sumatera Barat - Nadya Edlin; Armiati Armiati (Jurnal Ecogen, 2022)
This study aims to determine the effect of supervision and work discipline on employee performance at the Regional Development Planning Agency (BAPPEDA) of West Sumatra Province. This type of research is an associative descriptive study. The sampling technique used in this study was a saturated sample technique with a sample of 89 employees. The data analysis technique used in this research is path analysis. Based on the results of the analysis, it shows that work discipline as an intervening variable does not succeed in mediating the supervisory relationship as an exogenous variable on employee performance as an endogenous variable. In more detail, it can be concluded that: (1) the supervision of the leadership affects the work discipline of the Regional Development Planning Agency (BAPPEDA) of West Sumatra Province. This means that the better the supervision carried out by the leadership, the higher the work discipline of employees will be, and vice versa, (2) the supervision of the leadership affects the performance of employees at the Regional Development Planning Agency (BAPPEDA) of West Sumatra Province. This means that the better the supervision carried out by the leadership, the higher the performance produced by the employees, and vice versa. (3) Work discipline affects the performance of employees at the Regional Development Planning Agency (BAPPEDA) of West Sumatra Province. This means that the better the employee's work discipline, the higher the employee's performance will be, and vice versa..Keywords: supervision, work discipline, employee performance.